THE IMPLEMENTATION OF TEACHER’S MOTIVATIONAL STRATEGIES IN THE FREEDOM WRITERS MOVIE - Sheni Lustika; Syahrial Syahrial; Azwandi Azwandi (AL LUGHAH, 2021)
This research was aimed to know how the teacher motivates her learners and to observe the activities which were applied by the teacher in Freedom Writers movie. The method was descriptive qualitative analysis. The data was taken from the movie and its scripts. The data collection technique was documentation meanwhile the technique of data analysis is content analysis. The research findings were as follows; 1). The teacher employed 10 different motivational strategies. 2). The researcher found the various ways how the teacher applied the strategies in the classroom, those were; by giving respect, love, care and always motivate her learners, playing game, using song’s lyrics, writing assignment, switching the learners’ seat, field trip, discuss with some informants and give the support to the learners who got failed in their evaluation. However, all the kinds of those teacher’s strategies to motivate the learners which found in the movie can be used as references for the teacher in aspiring to be good educators in the future. Further study is recommended for a deeper investigation into teachers’ motivational strategies and their used in the classroom activities.